An effective image encryption algorithm based on compressive sensing and 2D-SLIM. (November 2020) - Xu, Qiaoyun; Sun, Kehui; He, Shaobo; Zhu, Congxu
Highlights: An image encryption algorithm based on compressive sensing and 2D-SLIM is proposed. Before compressive sensing, the row and column permutation is performed on the coefficient matrix to improve compression performance, and the diffusion algorithm based on GF (257) is designed to ensure the security of the compressed image. Simulation and performance analyses verify that the proposed scheme has good compression performance, high security under less sampling data. Abstract: This paper presents an image encryption algorithm based on the compressive sensing and a hyperchaotic map, which includes the permutation, compression and diffusion processes. Firstly, the plain image is transformed using discrete wavelet transform, and the coefficient matrix is obtained. Then, the row and column permutation are applied to achieve a good scrambling effect. Secondly, the permuted coefficient matrix is measured by a measurement matrix, and the measurement matrix is constructed using chaotic sequences generated by the 2D-SLIM map. Finally, the diffusion algorithm based on Galois field multiplication is designed to encrypt the compressed matrix, and the cipher image with small size and high security is obtained. What's more, the SHA-512 hash value of the plain image is introduced to set the initial values and parameters of the 2D-SLIM map to establish the correlation between the plain image and the algorithm, and it makes the algorithm can resist the known/chosen plaintext attacks. Furthermore, the row and column permutation before compressive sensing successfully improves the compression effect with low compression radio, and the diffusion operation improves the security of this algorithm. Simulations and performance analyses validate the good compression performance and high security of the proposed algorithm.